PENERAPAN MOTION TWEEN UNTUK ANIMASI DUA DIMENSI RUTE PERJALANAN BUS TRANS JOGJA - Nugrahenny, Dwi; Honggowibowo, Anton Setiawan; Mukti, Mega Lesya (Sekolah Tinggi Teknologi Adisutjipto, 2013)
Transportation is one of the important aspects in a region, where public transportation take effect on the mobility of the people. To achieve a good transportation can be create, so that the infrastructure and other supporting factors are needed. Yogyakarta municipality area has a lot of public transportasion, one of them is “Trans Jogja” bus, where each bus line has its route to reach any destination. It is needed a supporting media that can provide information about the route for each bus line so that people can be easily deciding which bus line that can use to reach their destination. Those information presented in the form of animation with an interesting and informative media. The use of animation as an information media that shown as a route trip, bus line including bus stop and departing passangers place assessed can be use as one of the other option for obtaining information except from a conventional map.